Fabrication and Characterization of Chitosan-Polypyrrole/Strontium-Magnesium Substituted Hydroxyapatite Biocomposite with Potential Application in Tissue Engineering Scaffolds - Lavanya, P.; Vijayakumari, N.; Sangeetha, R.; Priya, G. (Asian Journal of Chemistry, 2020)
Biocomposite scaffolds of strontium-magnesium substituted hydroxyapatite (SMHA) with a mixture of chitosan/polypyrrole (CS-PPY) have been prepared by solvent casting method. The synthesized SMHA nanoparticles and biocomposite scaffold were characterized by FTIR, XRD and SEM techniques. The SEM morphology revealed the porous structure of the scaffolds designed for the muticomponents. The biomineralization and cell viability of the biocomposite were assessed via alkaline phosphatase activity and MTT assay on the osteoblast cell line. The study demonstrated improved differentiation and mineralization of osteoblast cells in the designed biocomposite scaffolds. The dye stained fluorescent microscopic photographs apparent the good scattering and permeability of cells onto the scaffolds. However, biocomposite demonstrated good antibacterial activity and the excellent biocompatibility against osteoblast cells offers a possible route for the production of a biocomposite as a viable replacement for regenerative medicine scaffolding substance.